The burden of pertussis in older adults: what is the role of vaccination? A systematic literature review - Walid Kandeil; Petar Atanasov; Diana Avramioti; Josephine Fu; Nadia Demarteau; Xiao Li (Taylor & Francis Group, 2019)
Introduction: Pertussis (whooping cough) is a vaccine-preventable disease; however, neither natural- nor vaccine-induced protection is life-long. Although generally not severe in adults, pertussis can be associated with complications in patients with chronic conditions such as asthma or chronic obstructive pulmonary disease, and can be readily transmitted to more vulnerable populations, including neonates before they complete their primary vaccination. Furthermore, as the global population ages, the health and economic burden of the disease is expected to rise. Areas covered: A systematic literature review was conducted to ascertain the current epidemiological and financial burden of pertussis in older adults and to discuss the potential value of a booster vaccination in this population. Expert commentary: Our review indicates a considerable underestimation of the pertussis burden amongst older adults. Seroprevalence studies consistently demonstrate that the reported incidence may be much lower than the actual incidence. Tetanus toxoid-reduced diphtheria toxoid and acellular pertussis vaccines are immunogenic in older adults, induce high booster responses and are well-tolerated. There is therefore a good rationale for the advocacy of booster pertussis vaccination throughout life to prevent pertussis infection and its transmission, especially in adults aged ≥50 years.